Evaluation of ERIC-PCR as Genotyping Method for Corynebacterium pseudotuberculosis Isolates - Dorneles, Elaine M. S.; Santana, Jordana A.; Ribeiro, Dayana; Dorella, Fernanda Alves; Guimaraes, Alessandro S.; Moawad, Mohamed S.; Selim, Salah A.; Garaldi, Ana Luiza M.; Miyoshi, Anderson; Ribeiro, Márcio Garcia [UNESP]; Gouveia, Aurora M. G.; Azevedo, Vasco; et al. (Public Library Science, 2014)
The aim of this study was to evaluate the Enterobacterial Repetitive Intergenic Consensus (ERIC-PCR) as a tool for molecular typing of C. pseudotuberculosis isolates from eight different hosts in twelve countries. Ninety-nine C. pseudotuberculosis field strains, one type strain (ATCC 19410(T)) and one vaccine strain (1002) were fingerprinted using the ERIC-1R and ERIC-2 primers, and the ERIC-1R+ERIC-2 primer pair. Twenty-nine different genotypes were generated by ERIC 1-PCR, 28 by ERIC 2-PCR and 35 by ERIC 1+2-PCR. The discriminatory index calculated for ERIC 1, ERIC 2, and ERIC 1+2-PCR was 0.89, 0.86, and 0.92, respectively. Epidemiological concordance was established for all ERIC-PCR assays. ERIC 1+2-PCR was defined as the best method based on suitability of the amplification patterns and discriminatory index. Minimal spanning tree for ERIC 1+2-PCR revealed three major clonal complexes and clustering around nitrate-positive (biovar Equi) and nitrate-negative (biovar Ovis) strains. Therefore, ERIC 1+2-PCR proved to be the best technique evaluated in this study for genotyping C. pseudotuberculosis strains, due to its usefulness for molecular epidemiology investigations.